P1-S6.08 A multifaceted intervention to increase chlamydia testing in Australian general practice. (10th July 2011) - Hocking, J; Poznanski, S; Vaisey, A; Walker, J; Wood, A; Lewis, D; Guy, R; Temple-Smith, M
Abstract : Background: The Australian Government has funded the Australian Chlamydia Control Effectiveness Pilot (ACCEPt), a randomised controlled trial of a chlamydia testing intervention to assess the feasibility, acceptability and cost-effectiveness of chlamydia testing in general practice clinics. There are well documented barriers to increased chlamydia testing in general practice including time, cost, and clinicians' knowledge and awareness of chlamydia. If an intervention is to successfully increase chlamydia testing, it must minimise these barriers and take the uniqueness of each general practice into consideration. This paper describes the chlamydia testing intervention being implemented in ACCEPt. Methods: Clinics in the intervention group are being provided with a multifaceted evidence-based intervention designed to increase annual chlamydia testing for sexually active 16–29 year olds. The intervention includes: a computer alert prompting GPs to test; incentive payments for GPs and practice nurses to conduct testing; an annual recall system involving SMS, phone or mail reminders; a comprehensive education pack; and regular feedback on testing performance. The intervention will be in place for up to 4 years, and will be tailored to the resources and needs of each clinic. Prior to implementation, clinic staff are engaged and given the opportunity to identify methods for improving chlamydia testing within their clinic, using an evidence-based practice assessment tool. Results: To date, 69 clinics in 24 areas have been recruited across three Australian states. Four of these areas (9 clinics) have been randomised: two areas (7 clinics) are in the intervention group, and two areas (2 clinics) in the control group. The intervention has been customised to each clinic with two thirds of clinics receiving the computer alert, 4 clinics using SMS reminders for recall, others using a mail recall and some using practice nurses to initiate chlamydia testing. Where possible, doctors and practice nurses have been given one on one education and training about chlamydia and pelvic inflammatory disease. Conclusions: Given that each Australian general practice is unique, it is vital that the intervention is tailored to individual clinic needs to achieve sustainable system changes. This enables maximum staff engagement to ensure the effective uptake of increased chlamydia screening in the Australian general practice setting.